In my time : a personal and political memoir - Cheney, Richard B.; Cheney, Liz, 1966- (New York : Threshold Editions, 2011)
'In his unmistakable voice and with an insider's eye on history, former Vice President Dick Cheney tells the story of his life and the nearly four decades he has spent at the center of American politics and power'--
'A memoir from the former Vice President of the United States'--
Includes bibliographical references (p. [533]-539) and index.
Keywords: Cheney, Richard B; United States. -- Dept. of Defense -- Officials and employees -- Biography; United States. -- Congress. -- House -- Biography; Vice presidents -- United States -- Biography; Cabinet officers -- United States -- Biography; Legislators -- United States -- Biography; United States -- Politics and government -- 2001-2009.; United States -- Politics and government -- 1989-; United States -- Politics and government -- 1945-1989.